Effect of pre-coat solution temperature on fluidized bed urea coatings. (July 2015) - Naz, M. Y.; Sulaiman, S. A.; Ariwahjoedi, B.; Shaari, K. Z. K.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, coating properties of the native cassava starch were improved by reacting it with urea and di-sodium tetraborate. The FTIR spectroscopy was used to study the possible reaction mechanism of the coating formulation. The prepared starch dispersions were used to coat 3·45 mm urea granules in a swirling fluidised bed reactor. An in-house built fluidised bed with an intermittent top spraying facility was used to coat the urea beds fluidised above their minimum level of fluidisation. The pre-coat solution temperature was varied from 50 to 80°C and the corresponding coated urea samples were further characterised for their surface morphology, coating hardness and nitrogen release time. The SEM images revealed that the surface of the coated urea was harder, denser and smoother as compared to the uncoated urea. Significant improvements in mechanical parameters of coated urea were seen with an increase in solution temperature and mass of the di-sodium tetraborate. The overall nutrients release time of the coated urea in water was increased from 63·33 to 209 s. The surface hardness and coating thickness of coated urea was also increased with an increase in pre-coat solution temperature and di-sodium tetraborate mass in the coating composition.